SENSITIVITY OF THE IFA RAN GLOBAL CLIMATIC MODEL WITH AN INTERACTIVE CARBON CYCLE TO ANTHROPOGENIC INFLUENCE - Mokhov I.I.; Eliseev A.V.; Karpenko A.A. (My University, 2006)
The estimates of the sensitivity of the IFA RAN Global Climatic Model with an interactive carbon cycle to anthropogenic influence were obtained. In the numerical calculations using the IFA RAN model, anthropogenic emission of carbon dioxide into the atmosphere was specified on the basis of data from observations in 1860–2000, and according to the SRES-A2 and SRES-B2 scenarios for 2000–2100. Inclusion of the interaction with the carbon cycle into the global climatic model enhanced its temperature sensitivity to the increase of carbon dioxide emission into the atmosphere in the 21st century.